2010
DOI: 10.11646/zootaxa.2579.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Larval development of the shrimp Hippolyte sapphica d’Udekem d’Acoz, 1993 forma A and B (Decapoda: Caridea: Hippolytidae) reared in the laboratory, confirmation of the conspecific status of the two forms

Abstract: The complete series of larval staging of Hippolyte sapphica d’Udekem d’Acoz, 1993 forma A and B from Louros estuary was studied in the laboratory and described in detail for the first time. The reared larvae of H. sapphica passed through six zoeal stages and one megalopal stage. The larval monitoring completed when the individuals could be assigned clearly to form A and B via rostra formation. Under the experimental conditions, the average durations of the larval stages were as follows: three days for 1 st and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…This species inhabits shallow seagrass meadows in the central and eastern Mediterranean 2 , 44 , although forma B has only been reported from the Amvrakikos Gulf (Greece) and Venice Lagoon (Italy), always sympatric with forma A 45 . Larval development studies of both forms concluded that females of both forms can generate larvae ultimately developing in adults of either form 46 . The present phylogenetic analysis indeed corroborates that these forms belong to the same species with negligible differences in their genetic makeup.…”
Section: Discussionmentioning
confidence: 99%
“…This species inhabits shallow seagrass meadows in the central and eastern Mediterranean 2 , 44 , although forma B has only been reported from the Amvrakikos Gulf (Greece) and Venice Lagoon (Italy), always sympatric with forma A 45 . Larval development studies of both forms concluded that females of both forms can generate larvae ultimately developing in adults of either form 46 . The present phylogenetic analysis indeed corroborates that these forms belong to the same species with negligible differences in their genetic makeup.…”
Section: Discussionmentioning
confidence: 99%
“…This holds for the sexually differentiated specimens, as the form differentiation always precedes the sexual one (Ntakis et al . ), as well as for the juveniles, whose CL at the time of sacrifice was in the range 1.3–1.5 mm. At this size, no sign of transition from the short to the long rostrum type was observed anymore either in cultured or in wild individuals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the lack of other morphological differences, as well as on the same microdistribution over the habitat, d'Udekem d'Acoz () hypothesised that the two forms are conspecific, a hypothesis that has recently been confirmed (Ntakis et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations